Toxic reagents and expensive equipment: are they really necessary for the extraction of good quality fungal DNA? - Rodrigues, Paula (2018)
The aim of this work was to evaluate a fungal DNA extraction procedure with the lowest inputs in terms of time as well as of expensive and toxic chemicals, but able to consistently produce genomic DNA of good quality for PCR purposes. Two types of fungal biological material were tested - mycelium and conidia - combined with two protocols for DNA extraction using Sodium Dodecyl Sulphate (SDS) and Cetyl Trimethyl Ammonium Bromide as extraction buffers and glass beads for mechanical disruption of cell walls. Our results showed that conidia and SDS buffer was the combination that lead to the best DNA quality and yield, with the lowest variation between samples. This study clearly demonstrates that it is possible to obtain high yield and pure DNA from pigmented conidia without the use of strong cell disrupting procedures and of toxic reagents. Significance and Impact of the Study: There are numerous methods f or DNA extraction from fungi. Some rely on expensive commercial kits and/or equipments, unavailable for many laboratories, or make use of toxic chemicals such as chloroform, phenol and mercaptoethanol. This study clearly demonstrates that it is possible to obtain high yields of pure DNA from pigmented conidia without the use of strong and expensive cell disrupting procedures and of toxic reagents. The method herein described is simultaneously inexpensive and adequate to DNA extraction from several different types of fungi.